What's in a Copyright? The Forgotten Right to "Authorize" - Allen, Aden (Science and Technology Law Review, 2008)
For years, Congress and the Judiciary have wrestled with the problem of how to properly protect intellectual property rights while balancing them against the common good. One of the most active areas is that of indirect liability. The Patent Act of 1952 expressly codified liability for inducement and contributory infringement. However, the Copyright Act of 1976 failed to do the same. What should be made of Congress’ codification of indirect liability in patent but not copyright law? This Note will argue that indirect liability for copyright infringement can be derived from the 1976 Act’s use of the phrase “to authorize” when describing the exclusive rights of a copyright holder. This Note will consider the development of indirect liability in patent and copyright law, and compare the jurisprudence of America with that of Australia and England. Borrowing from the English and Australian copyright systems, this Note proposes that an appropriate authorization test would hold a party liable for (1) failing to take reasonable and effective measures to curtail infringement while (2) not enabling copyright owners to monitor infringement themselves. An additional authorization test would hold a party liable for granting or purporting to grant the authority to do an act exclusively reserved to the copyright owner. To highlight potential uses and effects of an authorization standard, this Note reviews the Supreme Court’s Grokster decision and compares two recent Ninth Circuit decisions. The Note concludes that the proposed authorization standard comports with the Copyright Act of 1976. However, the Note also suggests the need for Congress to provide greater guidance in the area.